Implementasi Teknik Sinematografi dalam Pembuatan Film Animasi 3D Cerita Rakyat “Batu Belah Batu Betangkup” - Rafi Mahendra; Anggy Trisnadoli; Erwin Setyo Nugroho (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Indonesia is a country that has a variety of people's literature one of which is packed in the form of folklore. One of the folklore in Riau Province is Batu Belah Batu Betangkup. Many people who do not know how the story in detail and public interest to know the story of the people is still very lacking. Many people today especially the younger generation only know the stories and figures from films coming from abroad. To overcome the above problems, then made a folklore film that is packed in the form of 3D animation. Folklore taken is a folktale that comes from the province of Riau is the folklore of Batu Belah Batu Betangkup. 3D animation film has a duration of about 20 minutes. The technique used in this 3D animated film is Cinematographic Technique, where the technique is used to capture the image and combine the image into one so as if the image is moving. Based on the results of testing and analysis, this film managed to recapture the public interest to know the folklore, the level of public knowledge about this folklore has increased significantly. Truth stories and cinematography techniques in 3D animation has been verified by experts.